Romances of the Archive in Contemporary British Fiction - Keen, Suzanne (Book collections on Project MUSE., 2003)
Romances of the Archive in Contemporary British Fiction is a lively discussion of the debates about the uses of the past contained in British fiction since the Falklands crisis. Drawing on a diverse and original body of work, Suzanne Keen provides a detailed examination of the range of contemporary 'romances of the archive, ' a genre in which British novelists both deal with the loss of Empire and a nostalgia for the past, and react to the postimperial condition of Great Britain. Keen identifies the genre and explains its literary sources from Edmund Spenser to H.P. Lovecraft and John LeCarre. She also accounts for the rise in popularity of the archival romance and provides a context for understanding the British postimperial preoccupation with history and heritage. Avoiding a narrow focus on postmodernist fiction alone, Keen treats archival romances from A.S. Byatt's Booker Prize-winning Possession to the paperback thrillers of popular novelists. Using the work of Peter Ackroyd, Julian Barnes, Lindsay Clarke, Stevie Davies, Peter Dickinson, Alan Hollinghurst, P.D. James, Graham Swift, and others, Keen shows how archival romances insist that there is a truth and that it can be found. By characterizing the researcher who investigates, then learns the joys, costs, and consequences of discovery, Romances of the Archive persistently questions the purposes of historical knowledge and the kind of reading that directs the imagination to conceive the past.